2010
DOI: 10.1523/jneurosci.1624-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Prime Actor in Humans during Bimanual Object Manipulation

Abstract: In bimanual object manipulation tasks, people flexibly assign one hand as a prime actor while the other assists. Little is known, however, about the neural mechanisms deciding the role assignment. We addressed this issue in a task in which participants moved a cursor to hit targets on a screen by applying precisely coupled symmetrical opposing linear and twist forces on a tool held freely between the hands. In trials presented in an unpredictable order, the action of either the left or the right hand was spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…In monkeys, these areas are also known to underlie arm/hand selection and control (Cisek and Kalaska, 2005; Hoshi and Tanji, 2004, 2006). Additionally, previous imaging results implicate these areas as important for planning and hand selection during bimanual object manipulation (Theorin and Johansson, 2010). …”
Section: Discussionmentioning
confidence: 84%
“…In monkeys, these areas are also known to underlie arm/hand selection and control (Cisek and Kalaska, 2005; Hoshi and Tanji, 2004, 2006). Additionally, previous imaging results implicate these areas as important for planning and hand selection during bimanual object manipulation (Theorin and Johansson, 2010). …”
Section: Discussionmentioning
confidence: 84%
“…suggested the involvement of different thalamic structures in the salience network (linked with limbic structures including insular cortices) and in the executive control network (involving prefrontal cortices). These networks are supposed to be involved in decision‐making processes, which could be relevant for parenting . Other authors related right thalamic activation with empathy .…”
Section: Discussionmentioning
confidence: 99%
“…This structure is considered important for the mother–infant bond in mammalian species, but the reason why is not clear and might be complex. In addition to empathy, thalamic involvement in salience and executive control network could be crucial for the decision‐making process involved in the parental activity . OT has been suggested to modulate salience of socio‐affective stimuli and several studies in both humans and animals suggested that OT might be involved in various decision‐making processes .…”
Section: Discussionmentioning
confidence: 99%
“…For example, switching roles across hands could prevent having to reorient or regrasp the object. This is particularly useful when the external task conditions change (38).…”
Section: From Unimanual To Bimanual Hand Pose Selectionmentioning
confidence: 99%